Ecotoxicity of Fire Retardants to Zebrafish (Danio rerio) in Early Life Stages - Darlan Quinta Brito; Tathyana Benetis Piau; Carlos Henke-Oliveira; Eduardo Cyrino Oliveira-Filho; Cesar Koppe Grisolia (Journal of Xenobiotics)
With the escalating frequency and intensity of global wildfires driven by climate change, fire retardants (FRs) have become essential tools in wildfire management. Despite their widespread use, the environmental safety of newer FR formulations—particularly in relation to aquatic ecosystems and developmental toxicity—remains insufficiently understood. In particular, their effects on fish embryos, which represent a sensitive and ecologically important life stage, are poorly characterized. This study investigated the acute toxicity of three commercially available FRs—N-Borate, N-Phosphate+, and N-Phosphate-—on early life stages of zebrafish (Danio rerio), based on an OECD 236 Fish Embryo Toxicity (FET) test. Notably, N-Phosphate- FR exhibited significant toxicity with a 96 h LC50 of 60 mg/L (0.0055%), while N-Borate (>432 mg/L, >0.032%) and N-Phosphate+ (>1181 mg/L, >0.08%) showed substantially lower toxicity. Sublethal effects, including reduced yolk sac absorption and yolk sac darkening, were observed across all FRs, highlighting potential developmental disruptions. The elevated toxicity of N-Phosphate- FR likely stems from its surfactant content. These findings reveal variations in the acute toxicity of different FR formulations, emphasizing the need for ecotoxicological assessments to guide the selection of safer FRs for wildfire management and to protect aquatic biodiversity. The results highlight the importance of incorporating developmental endpoints in FR risk assessments and provide foundational data for regulatory decisions regarding FR application near aquatic habitats. Further research is necessary to elucidate the mechanisms underlying observed effects and to evaluate cross-species toxicity at environmentally relevant concentrations.